Predict Repurchase Intention Via E-satisfaction as a Mediator Against Consumer Attitudes in Use Face Recognition Payment - Zahira, Nabila Alma; Kurniawati, Kurniawati (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2022)
In the last few decades, the use of technology has advanced and developed to enter the world of payments to make payments more manageable. Face Recognition Payment (FRP) is now being used as an option for in-store cashless payment methods. Based on the information system and customer theory, this study aims to predict repurchase intention through e-satisfaction as a mediator on consumer attitudes in using FRP. This study used an online questionnaire distributed to participants, with 239 valid responses received in Indonesia from May to June 2022. The data results were analyzed using different statistical methods, including descriptive statistics, reliability and validity analysis, and SEM-PLS. In this test, it can be concluded that consumer satisfaction is the main reason consumers make repeated purchases at stores that use the Face Recognition payment method. Furthermore, consumer attitudes toward the Face Recognition payment method can be influenced by the consumer's perceived personal risk and innovation. In contrast, the perceived usefulness and ease of use do not affect consumer attitudes toward the Face Recognition payment method. This study contributes to the literature by predicting consumer repeat purchases through perceived satisfaction as a mediator and providing new insights tailored to the needs of stores in an increasingly modern and growing market regarding consumer attitudes toward Face Recognition digital payments.